EFFECT OF WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE THROUGH MOTIVATION AT STARBUCKS COFFEE CIBUBUR BRANCH - Eddy Sanusi Silitonga (Dinasti Publisher, 2021)
This study aims to determine the performance of existing employees at Starbucks Coffee Cibubur Branch is influenced by the work environment through Motivation. This research was conducted on employees of the Starbucks Coffee Cibubur Branch. The research method used in this study is a data collection method used by distributing questionnaires to respondents or employees. This study uses the method of total sampling, or saturated sampling, where the sample used is all population members. The results of this study indicate that the work environment does not affect employee performance. Motivation affects employee performance. The work environment affects Motivation, and employee performance affects the work environment through Motivation. With these results,